Great big beautiful life [large type] - Henry, Emily (Thorndike Press large print top shelf., 2025)
"Two writers compete for the chance to tell the larger-than-life story of a woman with more than a couple of plot twists up her sleeve in this dazzling and sweeping new novel from Emily Henry. Alice Scott is an eternal optimist still dreaming of her big writing break. Hayden Anderson is a Pulitzer-prize winning human thundercloud. And they're both on balmy Little Crescent Island for the same reason: To write the biography of a woman no one has seen in years--or at least to meet with the octogenarian who claims to be the Margaret Ives. Tragic heiress, former tabloid princess, and daughter of one of the most storied (and scandalous) families of the 20th Century. When Margaret invites them both for a one-month trial period, after which she'll choose the person who'll tell her story, there are three things keeping Alice's head in the game. One: Alice genuinely likes people, which means people usually like Alice--and she has a whole month to win the legendary woman over. Two: She's ready for this job and the chance to impress her perennially unimpressed family with a Serious Publication. Three: Hayden Anderson, who should have no reason to be concerned about losing this book, is glowering at her in a shaken-to-the core way that suggests he sees her as competition. But the problem is, Margaret is only giving each of them pieces of her story. Pieces they can't swap to put together because of an ironclad NDA and an inconvenient yearning pulsing between them every time they're in the same room. And it's becoming abundantly clear that their story--just like the tale Margaret's spinning--could be a mystery, tragedy, or love ballad... depending on who's telling it"--